2010
DOI: 10.1111/j.1439-0531.2008.01307.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Immunolocalization of GLUTs 1, 2, 3 and 5 in Boar, Stallion and Dog Spermatozoa

Abstract: Spermatozoa, as other eukaryotic cells, need hexoses to produce energy to maintain membrane homeostasis, to move along the female genital tract and to carry the male genome to the female gamete. GLUTs are a family of proteins that permit and improve the passive transport of hexoses inside cells. This study was aimed at investigating the presence and localization of GLUTs 1, 2, 3 and 5 in boar, stallion and dog spermatozoa by both immunofluorescence and western blotting. GLUTs exhibited a peculiar distribution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 50 publications
3
38
0
Order By: Relevance
“…Regarding mammalian sperm, the first striking question is that focused on the specific distribution of these GLUTs along the sperm cell membrane. Thus, whereas GLUT1 is distributed along the entire tail and acrosome in boar and stallion sperm, the same hexose transporter is mainly located in the apical area of the acrosome in dog and donkey sperm, in the acrosome, midpiece, and principal piece of the tail in human sperm, and, finally, in the apical and acrosomal area of the head and the principal piece and final piece of the tail in rat and bull sperm [31][32][33]. Similar differences are also observed in the distribution of the other GLUTs, the circumstance being striking that the studied species that showed greatest differences in their overall GLUTs distribution when compared with the other studied species is dogs [32].…”
Section: Overview Of Mammalian Sperm Energy Metabolismmentioning
confidence: 98%
“…Regarding mammalian sperm, the first striking question is that focused on the specific distribution of these GLUTs along the sperm cell membrane. Thus, whereas GLUT1 is distributed along the entire tail and acrosome in boar and stallion sperm, the same hexose transporter is mainly located in the apical area of the acrosome in dog and donkey sperm, in the acrosome, midpiece, and principal piece of the tail in human sperm, and, finally, in the apical and acrosomal area of the head and the principal piece and final piece of the tail in rat and bull sperm [31][32][33]. Similar differences are also observed in the distribution of the other GLUTs, the circumstance being striking that the studied species that showed greatest differences in their overall GLUTs distribution when compared with the other studied species is dogs [32].…”
Section: Overview Of Mammalian Sperm Energy Metabolismmentioning
confidence: 98%
“…In pigs, Nichol et al (1992) reported that the concentrations of glucose were significantly lower in the whole oviduct (0.59 mM) than in the blood plasma (4.56 mM), but its concentration in the ampullary-isthmic junction during the preovulatory period (1.65 mM) was greater than during other periods of the estrous cycle. In boar sperm, the utilization of glucose is controlled in part by the heterogeneous localization of GLUT family transporters over the entire sperm surface (Bucci et al 2010). Sperm aldose reductase seems to be physiologically quiescent until sperm arrive in the cauda epididymis because the concentrations of the extracellular respiration substrates, glucose and fructose, are extremely low (Pruneda et al 2006).…”
Section: Role Of Aldose Reductase In Sperm Capacitationmentioning
confidence: 99%
“…These GLUT3 proteins were localized at the principal and end piece of the sperm tail, with the exclusion of the middle piece. However, the localization was different from the sperm of other mammals; for example, in boar, positive GLUT3 was evident in the acrosome and in a band across the middle of the sperm head (5,6,19,20). In bull sperm, the positive GLUT3 signal was present only in the middle piece (8,19).…”
Section: Discussionmentioning
confidence: 85%